Tingkat Kecemasan Siswa Sekolah Menengah Dalam Pertunjukan Musik - Marzam Marzam; Neviyarni Suhaili (FBS Universitas Negeri Padang, 2021)
The study aimed to measure Student Anxiety Levels in the Music Performance Anxiety Scale (MPAS) for high school (SMA) students with musical interests in Padang City, and to conduct studies on validity and reliability. In this case, the scale will be developed for use for middle school students (adolescents), and differences between the sexes will be examined. The research was conducted on 546 high school students. Of these students, 185 (33.9%) is male, 361 (66.1%) is female, and the average age is 16.81 with an age range of 15 to 20. The correlation value of scaled items between them and with the total items is checked as a preliminary analysis. As a result of the engineering of the EFA's main components, promax rotation techniques and their analysis, three-factor construction accounted for a total of 42.74% of the total variants achieved. The achieved structure is validated by the CFA, and a match index is found in the acceptance interval. In reliability studies, Alpha Cronbach's internal consistency coefficient was calculated as 0.86 for the entire scale, 27% for bottom-up group comparisons and re-test analysis conducted. T-tests were conducted to determine the difference between the sexes. As a result of the study, a valid and reliable visible scale has been developed and the differences between the sexes are clearly visible.